VLSI Technology: Revolutionizing Modern Communication Systems - Bharathi Guvvala, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative impact of Very Large Scale Integration (VLSI) technology on modern communication systems, examining its evolution, innovations, and future challenges. The article delves into how VLSI has revolutionized communication devices through miniaturization, integration density improvements, and power efficiency optimization. It investigates the crucial role of VLSI in enabling advanced mobile communications, network infrastructure, satellite systems, IoT devices, and next-generation wireless networks. The article analyzes the significant developments in signal processing and protocol implementation, highlighting how VLSI architectures have enabled sophisticated modulation techniques, error correction mechanisms, and real-time processing capabilities. Furthermore, it examines the semiconductor manufacturing ecosystem's evolution and its impact on communication technology advancement. The article also addresses emerging technologies like quantum computing and next-generation wireless networks, discussing technical challenges and potential solutions in VLSI communications. This article demonstrates how VLSI technology continues to be fundamental in shaping the future of communication systems, enabling unprecedented levels of connectivity and processing capabilities.
Keywords: VLSI Technology; Communication Systems; Semiconductor Manufacturing; Signal Processing; Quantum Computing Integration